MODEL SUPERVISI AKADEMIK KOLABORATIF: INTEGRASI KEMAMPUAN INTERPERSONAL DAN EFIKASI DIRI DALAM KONTEKS PENDIDIKAN - Tutik Sugesti; Astri Novia Sireggar (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to develop and analyze a collaborative academic supervision model that integrates interpersonal skills and self-efficacy in the educational context. With a descriptive qualitative approach and case study method, data were collected through in-depth interviews, observations, and documentation studies. The results of the study indicate that collaborative academic supervision can increase emotional involvement, intrinsic motivation, and self-confidence of teachers and students. Interpersonal skills are key to building positive relationships, while self-efficacy influences the effectiveness of supervision implementation. These findings recommend the application of a collaborative approach in supervision practices to create a supportive and productive academic climate